A Study of Stability of First-Order Delay Differential Equations Using Fixed Point Theorem Banach - Monje, Zaid A.A. Mahdi; Ahmed, Buthainah A.A. (Iraqi Journal of Science, 2019)
In this paper we investigate the stability and asymptotic stability of the zero solution for the first order delay differential equation where the delay is variable and by using Banach fixed point theorem. We give new conditions to ensure the stability and asymptotic stability of the zero solution of this equation.